Crafting an Integrated Curriculum: A Comprehensive Strategy for Early Childhood Education via Play-Based Learning - Forkpah, Eric; Lutfi, Ahmad (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
Early Childhood Education (ECE) faces global challenges in providing a universally comprehensive curriculum, potentially leading to developmental deficiencies in young learners. Past studies in Montserrado County, Liberia, highlighted gaps in cognitive, social, emotional, and physical development due to the absence of a structured and holistic curriculum. This research aimed to develop and implement a comprehensive curriculum emphasizing play-based learning strategies, considering local educational practices and cultural dynamics. Drawing from Dewey's educational philosophy, the study focused on transformative, child-centered approaches. Through purposive sampling and qualitative analysis, the study examined engagement levels, cognitive outcomes, socio-economic factors, community perceptions, implementation challenges, and recommendations. Findings revealed positive engagement in play-based learning, though resource disparities existed. Cognitive gains were noted, with socio-economic backgrounds influencing outcomes. Community support was strong but with reservations. Implementation challenges included resource constraints and teacher comfort levels. Recommendations emphasized continuous professional development and strategic resource allocation. Overall, the study highlights the potential of play-based learning to enhance early childhood education, offering insights for Montserrado County and broader implications for similar contexts globally.